2009
DOI: 10.1017/s0021859609008673
|View full text |Cite
|
Sign up to set email alerts
|

Rumen phosphorus metabolism in sheep

Abstract: SUMMARYThe objective of the present study was to examine the effect of the level of phosphorus (P) intake on ruminal P kinetics in sheep. Twelve Santa Inês male sheep (average body weight 36 kg) were fed a basal diet consisting of roughage (coast cross hay), concentrate mixture (cassava meal, soya bean meal and urea) and a mineral premix. The treatments consisted of the basal diet supplemented with 0, 1·5, 3 or 4·5 g/kg dry matter (DM) of mono-ammonium phosphate to provide increasing P levels representing trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 29 publications
1
7
0
1
Order By: Relevance
“…Ruminants may be different because they recycle P into the rumen via saliva to provide P to their micro‐organisms (Dias et al., ; Engelhardt & Breves, ) and therefore might not need to remove Ca from the digestive tract; their faeces typically contain higher Ca concentrations and Ca/P ratios than those of hindgut fermenters (Schryver et al., ). In addition, in ruminants, renal P excretion shows considerable interindividual variation that appears to be higher than in other species (Taube, ; Taube, Rohn, Kreienbrock, & Kamphues, ).…”
Section: Introductionmentioning
confidence: 99%
“…Ruminants may be different because they recycle P into the rumen via saliva to provide P to their micro‐organisms (Dias et al., ; Engelhardt & Breves, ) and therefore might not need to remove Ca from the digestive tract; their faeces typically contain higher Ca concentrations and Ca/P ratios than those of hindgut fermenters (Schryver et al., ). In addition, in ruminants, renal P excretion shows considerable interindividual variation that appears to be higher than in other species (Taube, ; Taube, Rohn, Kreienbrock, & Kamphues, ).…”
Section: Introductionmentioning
confidence: 99%
“…As the salivary glands can concentrate P i from plasma by a factor of up to 16, approximately 50% of rumen P i can origin from saliva (Breves & Schröder, 1991; Read, Engels, & Smith, 1986). Although a tight correlation could be demonstrated between blood plasma and saliva P i concentrations (Mañas‐Almendros et al., 1982; Valk, Šebek, & Beynen, 2002), some controversy exists as to whether salivary P i secretion is regulated in order to maintain P i homeostasis or to ensure rumen microbial growth (Dias et al., 2009; Kebreab et al., 2005). As expected, we found a reduction in both salivary and rumen P i concentrations with dietary P restriction (Table 3), but a positive linear correlation between serum and salivary P i was only revealed in the control group (Figure 4).…”
Section: Discussionmentioning
confidence: 99%
“…In ruminants, the amount of mineral excreted varies according to the type of diet. The amount and the source of phosphorus used in the diet also affect the kinetics of the mineral in the body [39,40]. The age of the animal can influence the use of dietary phosphorus, since it has been observed that young animals have higher absorption efficiency [41].…”
Section: Discussionmentioning
confidence: 99%